Rendahnya Minat Wirausaha Mahasiswa Program Studi Ekonomi Syariah STAI Al-Ittihad Cianjur - Yulia Eka Rini; Hendarsyah; Moch Agniya Wahda (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
The phenomenon of low entrepreneurial interest among students of the Sharia Economics Study Program at STAI Al-Ittihad Cianjur can be seen from the fact that many of them prefer to work as employees or even laborers rather than becoming entrepreneurs because of their prestige and lack of self-confidence. The purpose of writing this scientific work is to determine the factors causing the low entrepreneurial interest of students in the Sharia Economics Study Program at STAI Al-Ittihad Cianjur. This scientific work research uses descriptive qualitative research with a phenomenological approach with data collection techniques in the form of interviews and literature studies. The results of this scientific work research show that the factors that cause students' low interest in entrepreneurship come from themselves (internal factors) and the causes that come from outside themselves (external factors). Internal factors include prestige, lack of self-confidence, feeling unable to attract consumers, choosing to become an employee, fear of competition and fear of taking risks. Meanwhile, the external factor is not having capital.